Chronic migraine prevention from the perspective of a family doctor: a literature review - Żymła, Tatiana; Pokładnik, Dominika; Szczerba, Jakub; Podsiedlik, Adam; Poloczek, Alicja; Stefanowicz, Agata; Jeleń, Katarzyna; Pokora, Szymon; Sojka, Paweł; Pokora, Karolina (Journal of Education, Health and Sport, 2024)
Chronic migraine is a disease that significantly reduces the quality of life of patients. It affects millions of people around the world, and is common particularly among young women. Family physicians often encounter the problem of migraine headaches in their daily practice. The diagnostic problem results from absence of tests or imaging studies that can clearly indicate the cause of the headache. In order to establish a diagnosis and exclude secondary sources of pain, doctors focus on a detailed medical history and analysis of symptoms presented over time. Preventive treatment of migraine requires appropriate drug selection after weighing the benefits and risks for each patient. This review paper presents and briefly discusses selected pharmacological and non-pharmacological methods used in migraine prevention. They were selected by searching the PubMed Internet database. The presented non-pharmacological methods include the use of nutraceutics, acupuncture and behavioral therapy. The discussed pharmacological methods include treatment with beta-blockers, topimarate, flunarizine or one of the latest methods - the use of monoclonal antibodies against CGRP. In addition, the use of botulinum toxin type A in the treatment of chronic migraine has also been demonstrated. It should be remembered that the type of therapy chosen should be individualized: according to the patient's preferences, treatment effectiveness, possible side effects or accompanying diseases. Proper management of chronic migraine prophylaxis can significantly improve the quality of life of patients and reduce the frequency of headache attacks.